Penggunaan permainan puzzle pada materi bangun datar di kelas VII SMP Negeri 12 Yogyakarta - Noor Laila Atini (STKIP PGRI Banjarmasin, 2018)
This study aims to describe how student activity in application of puzzle game media on the material wake flat in class VII SMP Negeri 12 Yogyakarta. In addition, this study also aims to determine the results of learning and student response with the application of these media. The method used in this research is descriptive research method. The study was conducted in SMP Negeri 12 Yogyakarta with 36 students. Data collection techniques used include tests, observations, and questionnaires. The results of this study indicate that the application of puzzle game media on the flat wake material can be said to work well, because it produces a positive influence for students. Students' learning outcomes with the puzzle game media provide an enhanced view of the completeness level. In addition, students' responses to learning mathematics by using puzzle games show very strong response qualifications, meaning students feel happy and enthusiastic in applying the game.